2020
DOI: 10.30968/rbfhss.2020.113.0487
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines for management of chemotherapy-induced nausea and vomiting in a tertiary public hospital

Abstract: Peer review: blind reviewer and Annemeri Livinallli Objectives: To assess if the antiemetic prophylaxis prescribed to patients exposed to chemotherapy is following the Antiemesis guideline published by the National Comprehensive Cancer Network (NCCN) version 3.2018. Methods: A medication review was performed, considering antiemetic´s prescriptions of adult patients under treatment with moderate and high emetogenic potential antineoplastic agents, assisted on an outpatient basis in a tertiary public hospital, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…It is also necessary to expand access to antiemetics and to implement strategies to increasing adherence to the guideline's recommendations by the prescribers. 19 This study also showed an association between nausea and vomiting with women as well as association between nausea and non-elderly patients. It is in agreement with a recent systematic review that reported that female sex and younger people are at higher risk for chemotherapy-induced nausea and vomiting.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It is also necessary to expand access to antiemetics and to implement strategies to increasing adherence to the guideline's recommendations by the prescribers. 19 This study also showed an association between nausea and vomiting with women as well as association between nausea and non-elderly patients. It is in agreement with a recent systematic review that reported that female sex and younger people are at higher risk for chemotherapy-induced nausea and vomiting.…”
Section: Discussionsupporting
confidence: 60%
“…It is also necessary to expand access to antiemetics and to implement strategies to increasing adherence to the guideline’s recommendations by the prescribers. 19…”
Section: Discussionmentioning
confidence: 99%
“…As the adverse events commonly reported in the use of antineoplastic drugs are chemotherapy-induced nausea and vomiting (CINV), these drugs are classified according to their emetogenic potential ( 8 ) , and the one with the greatest emetogenic potential characterizes the protocol. Therefore, Cyclophosphamide is a drug with a high emetogenic potential and Oxaliplatin has a moderate emetogenic potential ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Como os eventos adversos comumente relatados na utilização de quimioterápicos são as náuseas e vômitos induzidos por quimioterapia antineoplásica (NVIQA), esses fármacos são classificados segundo seu potencial emetogênico (8) , e aquele de maior potencial emetogênico caracteriza o protocolo. Assim, a Ciclofosfamida é um fármaco de alto potencial emetogênico e a Oxaliplatina de moderado potencial emetogênico (9) .…”
Section: Introductionunclassified